Lipase immobilized on poly(VP-co-HEMA) hydrogel for esterification reaction - Basri, Mahiran; Samsudin, Sunana; Ahmad, Mansor; Abdul Razak, Che Nyonya; Salleh, Abu Bakar (Humana Press, 1999)
Lipase from Candida rugosa was immobilized by entrapment on poly(N- vinyl-2-pyrrolidone-co-2-hydroxyethyl methacrylate) (poly[VP-co-HEMA]) hydrogel, and divinylbenzene was the crosslinking agent. The immobilized enzymes were used in the esterification reaction of oleic acid and butanol in hexane. The activities of the immobilized enzymes and the leaching ability of the enzyme from the support with respect to the different compositions of the hydrogels were investigated. The thermal, solvent, and storage stability of the immobilized lipases was also determined. Increasing the percentage of composition of VP from 0 to 90, which corresponds to the increase in the hydrophilicity of the hydrogels, increased the activity of the immobilized enzyme. Lipase immobilized on VP(%):HEMA(%) 90:10 exhibited the highest activity. Lipase immobilized on VP(%):HEMA(%) 50:50 showed the highest thermal, solvent, storage, and operational stability compared to lipase immobilized on other compositions of hydrogels as well as the native lipase.